Pengaruh Pembelajaran Literasi Digital terhadap Minat Belajar Siswa di Tingkat Sekolah Dasar - Afriyana, Afriyana; Salamah, Siti; Enjelina, Della; Saputra, M. Riski (Lembaga Yasin AlSys, 2023)
Digital literacy learning is important in today's digital era, especially at the elementary school level. Digital literacy involves using skills in using digital technology and managing information effectively. In a short time, digital technology has changed the way we learn and work. Therefore, it is important to understand the effect of digital literacy learning on students' interest in learning at the elementary school level. The purpose of this study was to evaluate the effect of digital literacy learning on students' interest in learning at the elementary school level. The research method used in this study is a qualitative research method with a literature review design. Data analysis was carried out by identifying the main findings from previous studies.